Designing the digital transformation : 12th International Conference, DESRIST 2017, Karlsruhe, Germany, May 30? June 1, 2017, Proceedings /: 12th International Conference, DESRIST 2017, Karlsruhe, Germany, May 30? June 1, 2017, Proceedings. (2017) - Unknown
No abstract available